PERBEDAAN RERATA KADAR HEMOGLOBIN IBU HAMIL DI DAERAH ENDEMIS DAN NON-ENDEMIS MALARIA PROVINSI LAMPUNG - Ulima Mazaya Ghaisani; Jhons Fatriyadi Suwandi; Tri Umiana Soleha; Betta Kurniawan (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2019)
Background: The Annual Parasite Incidence (API) malaria 2014 in Hanura Public Health Center, Pesawaran Regency was 48,75‰ which is classified as high endemisity meanwhile API malaria in Rajabasa Indah Public Health Center, Bandar Lampung City was 0,00‰ which is classified as non-endemic. Malaria in pregnant women can directly causes anemia maternal because of the destruction of erythrocytes that contain parasites and which are not, reduction of survival time, and dyseritropoiesis. The highest prevalence of anemia materna in Sumatra is Lampung Province with 25,9%. The aim: aim of this study is to differ mean hemoglobin level of pregnant women in endemic and non-endemic malaria in 2016. The method: Method which used in this study is an comparative with cross-sectional which included 104 pregnant women in Hanura and Rajabasa Indah Public Health Center in 2016. This study uses primary data which taken from pregnant women‘s peripheral blood. Research findings: Results of the study showed pregnant women with low hemoglobin level are more happening in endemic malaria with 67,3% women than in non-endemic malaria with 34,6% women. The result with Mann-Whitney test shows there has diverication between mean haemoglobin level of pregnant women (p=0,014) who are living in endemic and non-endemic malaria. The conclusion: Shows a diverication of mean hemoglobin levels of pregnant women in endemic and non-endemic malaria in Lampung Province.